2012
DOI: 10.1007/s00268-012-1775-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of 18F‐Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in Predicting the Pathologic Response to Preoperative Chemoradiation Therapy in Patients With Resectable T3 Pancreatic Cancer

Abstract: A better pathological response can be expected for pancreatic cancer patients who have a high regression index (≥ 0.46) and a high pre-CRT SUV (≥ 4.7). The SUV measurement using FDG-PET/CT is a useful tool for predicting the pathologic response to preoperative CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 55 publications
0
43
0
Order By: Relevance
“…Only one study that showed a correlation with FDG-PET parameters with treatment response was found. Higher baseline SUV max was associated with a histopathological response – the predictive function of FDG-PET in this series was increased by combining the baseline SUV max with the relative SUV response after CRT [44]. It should be noted that this series defined histopathological response as <50% viable tumour cells seen in a resection specimen.…”
Section: Resultsmentioning
confidence: 72%
“…Only one study that showed a correlation with FDG-PET parameters with treatment response was found. Higher baseline SUV max was associated with a histopathological response – the predictive function of FDG-PET in this series was increased by combining the baseline SUV max with the relative SUV response after CRT [44]. It should be noted that this series defined histopathological response as <50% viable tumour cells seen in a resection specimen.…”
Section: Resultsmentioning
confidence: 72%
“…The past literature demonstrated that it can be difficult to evaluate local tumor progression accurately by radiological evaluation after chemotherapy and/or chemoradiation therapy [14]. And the other studies have shown that tumor markers or PET findings are sometimes helpful in estimating the efficacy of anti-cancer therapy [15, 16]. However, in this case, tumor markers were not increased and PET findings were normal before the first-line treatment.…”
Section: Discussionmentioning
confidence: 87%
“…A regression index > 0.46 was observed in 15 (71%) responders and 5 (26%) nonresponders. It showed that the SUV based on FDG-PET/CT is a useful implement for predicting the response of treatment [39] .…”
Section: Staging: Wang Et Almentioning
confidence: 99%
“…Results showed that PET/CT play more important factors in designing the treatment plans for individual patient than conventional CT [38] . Kittaka et al [39] performed 18 F-FDG PET in patients classified as responders and nonresponders before and after preoperative CRT. A pre-CRT SUV > 4.7 was seen in 15 (71%) of 21 responders and in 6 (32%) of 19 nonresponders.…”
Section: Staging: Wang Et Almentioning
confidence: 99%